2006
DOI: 10.1111/j.1461-0248.2005.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of climate change in coastal marine systems

Abstract: Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate-related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
1,519
0
29

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,236 publications
(1,562 citation statements)
references
References 109 publications
(222 reference statements)
14
1,519
0
29
Order By: Relevance
“…changes in climate, atmospheric composition in terms of CO 2 and nitrogen compounds, changing land use) and the associated feedback effects are likely to represent one of the largest uncertainties in projections of future biodiversity change [89,90] and will have profound impacts on research into global change and ecosystem management. The same applies for indirect impacts, as for example for aquatic environments the effects of changing temperatures on water column stratification, changes in ocean currents, pH, or upwelling, adding further question marks to the longer-term development of ecosystems under climate change [91].…”
Section: Consequences Of Climate-mediated Invasionsmentioning
confidence: 99%
“…changes in climate, atmospheric composition in terms of CO 2 and nitrogen compounds, changing land use) and the associated feedback effects are likely to represent one of the largest uncertainties in projections of future biodiversity change [89,90] and will have profound impacts on research into global change and ecosystem management. The same applies for indirect impacts, as for example for aquatic environments the effects of changing temperatures on water column stratification, changes in ocean currents, pH, or upwelling, adding further question marks to the longer-term development of ecosystems under climate change [91].…”
Section: Consequences Of Climate-mediated Invasionsmentioning
confidence: 99%
“…With this we mean that measures for protecting or restoring coastal ecosystems need a broad approach addressing cumulative impacts that traditionally are managed by separate management sectors: including restoration of offshore food webs, improvements in water quality and increased habitat protection through implementation of marine protected areas . Furthermore, changes in offshore and coastal food webs co-occur with major changes in large-scale hydrodynamics and transport through human engineering and climate change (Harley et al 2006;Eriksson et al 2010), external nutrient loading by eutrophication (Cloern 2001) and habitat destruction through coastal development and dredging (Airoldi and Beck 2007). Therefore, cascading effects of increases in mesopredator abundances will most likely interact with other human-driven changes in environmental conditions and abiotic resources, eventually altering the functions of coastal communities (Fig.…”
Section: Managing Interactions Between Nearshore Communities and Offsmentioning
confidence: 99%
“…Declining populations of stationary piscivores and/or limited migrations of offshore piscivorous fish to nearshore areas in combination with increasing resource loads, may enhance bottom-up control of the nearshore ecosystem. Specific effects of climate change are not well understood (Harley et al 2006) the Pacific and the western Atlantic also support that offshore trophic cascades or changes in migration patterns of offshore predators, can have cascading effects on coastal food-webs (reviewed in Baum and Worm 2009). Thus, the offshore coastal linkages described in our study systems may be relevant for a wide range of developed coasts that border highly exploited offshore systems.…”
Section: Managing Interactions Between Nearshore Communities and Offsmentioning
confidence: 99%
“…Existing 20th century global climate change of 0.6 ± 0.2°C has already resulted in significant ecological changes across an expanse of different ecosystems and ecological hierarchies (McCarty 2001, Walther et al 2002, Ward et al 2005, Hoegh-Guldberg et al 2007, Prezeslawski et al 2008. These responses are expected to accelerate, resulting in habitat degradation, species loss and range changes caused by increases in temperature (McCarty 2001, Poloczanska et al 2007, storm frequency and intensity (Harley et al 2006, Crabbe et al 2008) and acidification of aquatic environments (Kleypas et al 1999, Orr et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of the influence of climate change scenarios on seagrass (Short & Neckles 1999, Harley et al 2006, Poloczanska et al 2007, Waycott et al 2007) are largely based on incidences of seagrass loss associated with extreme weather (Cardoso et al 2008, Micheli et al 2008 as reported in short-term experimental studies (Campbell et al 2006). Long-term studies directly measuring seagrass changes and how they are correlated with climate are rare.…”
Section: Introductionmentioning
confidence: 99%